When Lawyers Shut Up: The Law Society of Kenya’s Silence during the Colonial Era - Muyumbu, Gilbert; Matheka , Reuben; Nyakwaka , Dorothy (African Journal of Education,Science and Technology (AJEST), 2024)
This paper explores moments when the Law Society of Kenya (LSK) remained silent in the face of excesses of the colonial administration. The LSK is an important agent in restraining the Kenyan state from violations against the rule of law. Yet since its emergence in the 1920s as a premier lawyers’ organisation, this has not always been the case. The organisation has had episodes of silence in the face of state violation of the rule of law. The paper conceptualizes the rule of law as implying checks and balances, existence of rules which apply to everyone and respect for due process, and silence as constituting LSK actions which were inadequate in countering given state excesses. It uses entanglement, sourced from the poststructuralist intellectual tradition, along with related concepts of ambivalence and hybridity as well as conviviality, as the conceptual framework to explain LSK’s silence in the face of colonial government excesses. Further, the paper employs the ex post facto research design and uses available archival accounts as sources of primary data and books and journals for secondary data to establish what constituted the most egregious violations of the rule of law under colonial rule. It also identifies LSK’s reaction to the violations, whether this was through pronouncements, actions or non-action. The paper also examines the dynamics which informed the organisation’s reaction. It concludes by elaborating on the organisation’s character as a result of the silence, challenging assumptions that it was a consistent defender of the rule of law in Kenya across time.